Teaching Spanish in high-context and low-context cultures: English speakers and Chinese speakers - Sánchez-Bermúdez , Adelí (2023)
The aim of this study is to evidence the importance to know the difficulties that implies the Spanish teaching and learning in high and low context cultures. This promotes a better communication between people and it promotes the dissemination of knowledge and a better global conviviality. This research will be focused in giving relevant information that will help in the teaching process for the Spanish teachers as a foreign language for English and Chinese speakers. This research presents a qualitative approach and was conducted through the triangulation of expert interviews, documentary analysis and anecdotal records. This study demonstrated that there is no single learner profile that contemplates valid characteristics for all Chinese and English-speaking learners, nor is there any magic recipe that facilitates the respective teaching-learning process. However, it is important to pay attention both to the normative aspects of the language and to the pragmatic aspects that lead us to speak a language in the mental and social scheme of another culture